EVALUASI PENERAPAN REKAM MEDIS ELEKTRONIK BAGIAN PENDAFTARAN DI KLINIK PRATAMA MADANI TASIKMALAYA - Yuyun Yunengsih; Irma suryani; Yuda Syahidin (Media Bina Ilmiah, 2024)
Background: Electronic Medical Records (RME) is a supporting technology that allows users to provide fast, precise and quality services compared to paper-based medical records. One of the providers of health services is a clinic. The Registration Department is one of the work units in the Clinic. The implementation of RME at the Pratama Madani Clinic has gone well so far. Objective: The aim of this research is to evaluate the implementation of electronic medical records in the Registration section at Pratama Madani Clinic Tasikmalaya. Method: The research method used is qualitative analysis with a descriptive approach. The data collection techniques used were observation, interviews and literature study. This research software system uses the waterfall development method which includes requirements analysis, system design, coding, testing and maintenance phases. The system design was developed using flowmaps, context diagrams and DFD Results: Several research results show that the Paratama Madani Clinic has been running well but has not fully implemented the use of electronic medical records. There are still several problems and shortcomings, namely inadequate facilities and infrastructure, the absence of special staff or teams to handle the implementation of electronic medical records, and the absence of written policies and fixed SOPs. Conclusion: Pratama Madani Clinic has not fully implemented RME because there are still several weaknesses and deficiencies in the system used and inadequate facilities